2017
DOI: 10.1007/s13213-017-1311-1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of pathogenic bacteria in ice cubes and evaluation of their survival in different systems

Abstract: In this study, 60 samples of ice cubes produced at different levels (domestic, restaurant and industrial facilities), within a restricted geographical area, were investigated for their general microbiological characteristics through the analysis of populations other than enteric bacteria. Total mesophilic bacteria were in the range 1.01 × 10 2 -9.55 × 10 3 , 3.12 × 10 2 -6.31 × 10 3 and 1.30 × 10 2 -3.99 × 10 3 CFU/ 100 mL of thawed ice from domestic freezer (DF), stock boxes (SB) for self-production performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…For this reason, the application of disinfection methods is necessary to reduce the microbiological risks related to drinking water [3] and its transformation products. The product obtained directly from potable water through the application of the freezing process is referred to as "food grade ice" or most commonly "food ice" [4]; this product is generally available for consumption in the form of cubes [5]. After melting, food ice becomes potable water [6] and it has to satisfy the minimum requirements on the hygiene of foodstuffs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the application of disinfection methods is necessary to reduce the microbiological risks related to drinking water [3] and its transformation products. The product obtained directly from potable water through the application of the freezing process is referred to as "food grade ice" or most commonly "food ice" [4]; this product is generally available for consumption in the form of cubes [5]. After melting, food ice becomes potable water [6] and it has to satisfy the minimum requirements on the hygiene of foodstuffs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial food ice is produced worldwide using ice machines and is commercialized after packing in plastic bags. Often, the quality and safety of packaged food ice does not meet the hygienic standards requested for drinking water [8] and this is imputable to improper handling during production [9], post-production contamination by the transformation environment [4], and to the packaging [10]. As a result, several microorganisms can be found in food ice, mainly intestinal bacteria [5,11,12], but also unicellular and filamentous fungi [13].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide food ice production has increased in recent years because of the high demand for ice cubes in public places such as bars, pubs and restaurants. Today, commercial ice production is estimated at around 500,000 tonnes per year in Europe and 5,600,000 tonnes per year in the United States [1]. Used in large quantities mostly in the summer, ice is useful in restorative and commercial activities for preparing cold drinks, and helps to maintain the cold chain that is very important for multiple foods, including fish and other foods eaten raw.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the microbiological quality of food ice and have confirmed its potential role as a vehicle for foodborne illnesses. In fact, Enterobacteriaceae, Enterococci and fungi have been isolated from ice in Italy [1,6,7]; total and faecal coliforms, Clostridium perfringens, Pseudomonas aeruginosa, Yersinia spp. and Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…and Salmonella spp. (Falcão, Dias, Correa, & Falca, ); Pseudomonas , Staphylococcus , Bacillus , and Acinetobacter (Settanni et al, ); Hepatitis A virus (Beller, ); Norovirus (Khan et al, ) and Vibrio Cholera (Ries et al, ; Waturangi, Pradita, Linarta, & Banerjee, ). Several factors have been linked to microbiological contamination of ice, namely: use of contaminated water for its production (Lateef, Oloke, Kana, & Pacheco, ; Northcutt & Smith, ), storing conditions, unsanitary ice handling, production and transportation procedures, type of use and production equipment (Awuor, Thompson, Thompson, Liberda, & Meldrum, ; Gerokomou et al, ; Nichols & Gillespie, ; Wilson, Hogg, & Barr, ).…”
Section: Introductionmentioning
confidence: 99%